CHARACTERISTICS OF PEOPLE WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE OF PRIMARY HEALTH CARE (Fiep Bulletin - online, 2015)
The study aimed to characterize people with chronic obstructive pulmonary disease enrolled in two health centers. It is an exploratory and descriptive study, conducted through individual interviews using a structured questionnaire, at homes of the people. The structured questionnaire was composed of data such age, sex, race, level of education, marital status, current occupation, salary, risk factors, associated diseases, degree of lung function impairment, type of treatment, expenses for the treatment and use of health centers. Data analysis was by descriptive statistics using percentage, mean and standard deviation. The sample consisted of 22 people, all caucasians, mostly female, married, low education, retired, ex-smokers, with associated diseases, aged 41 to 81 years and receiving from one to six Brazilian minimum salary. The disease predominantly people with severe lung function. The predominant treatment was medical consultation with prescription medications, with high costs for treatment. The health centers are used more during periods of acute exacerbations of the disease. It was concluded that there is a need to plan for the Health Care Programs in primary health care, directed for people with chronic obstructive pulmonary disease to provide an interdisciplinary treatment and health education that promotes autonomy of the subject and encouragement of continued treatment.
Keywords: Primary Care; Chronic Obstructive Pulmonary Disease; Basic Health Services